A Contemporary Review of Evidence for Transoral Robotic Surgery in Laryngeal Cancer - Gorphe, Philippe (Frontiers in Oncology, 2018)
Numerous studies have shown that transoral robotic surgery (TORS) for oropharyngeal cancers is safe and that it yields satisfactory functional and oncological outcomes. For many teams worldwide, it is therefore a standard surgical approach with eligible patients. In the same time, TORS is increasingly being used and described in the context of laryngeal cancer surgery. It is proposed as an alternative to open approaches, which may yield inconsistent functional results and significant rates of postoperative complications. It may also be an alternative to definitive radiotherapy, which entails significant early and late toxicities. Moreover, it has been explored as an alternative to endoscopic laser surgery in patients with difficult exposure, even though there is still a lack of evidence about which procedure provides better vizualization of the vocal cords. This article provides a review of the indications for TORS in laryngeal cancer, the peri-operative morbidity, functional outcomes, and oncological results.